Exertional heat stroke in an amateur runner - Challenges in diagnostics and the role of unhealthy competition - Marlega, J.; Mickiewicz, A.; Fijalkowska, J.; Gruchala, M.; Fijalkowski, M. (Journal of Sports Sciences, 2020)
Exertional heat stroke (EHS) is a potentially life-threatening condition with a variety of symptoms and abnormal laboratory findings. Nevertheless, data evaluating the course of making an EHS diagnosis in real-life practice, as well as the role of predisposing psychological components are limited. Thus, the aim of our study was to present a multi-faceted differentiation process and show the role of unhealthy competition in the development of EHS.